40. STATUS OF COMPLIANCE WITH VENOUS BLOOD DRAWING PROCEDURES BY NURSES AND SOME AFFECTING FACTORS AT VIET YEN TOWN MEDICAL CENTER, BAC GIANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current situation and analyze factors influencing compliance with venous blood sampling (VBS) procedures among nurses at Viet Yen Town Medical Center, Bac Giang Province, in 2024.Subjects and Methods: A cross-sectional study combining quantitative and qualitative methods was conducted among nurses working at the Center.Results: The overall compliance rate with the VBS procedure was 53.2%. Several steps showed relatively high adherence rates (above 70%), including nurse preparation, equipment preparation, patient preparation, correct needle insertion, transferring blood to test tubes, and post-procedure cleanup. Two steps showed a 60% compliance rate: site preparation and procedure completion. Hand hygiene was the most frequently omitted step (64%). Other steps with lower compliance included patient instruction (70%), rapid hand disinfection (80%), and correct skin tensioning technique (80.8%). Key influencing factors included substandard infrastructure (room size, lighting, air conditioning), lack of equipment (e.g., blood collection tubes), and insufficient supervision with no regular assessment of staff competencies.Conclusion: Compliance with the VBS procedure among nurses remains suboptimal, particularly in hand hygiene. Improvements in working conditions, availability of equipment, and enhanced supervision are needed to ensure better practice quality.
Keywords: Venipuncture procedure; nurse